Insecticide-treated net utilization and associated factors among pregnant women in Ethiopia: a systematic review and meta-analysis - Eshetu, Bajrond; Bekele, Habtamu; Debella, Adera; Eyeberu, Addis; Balis, Bikila; Habte, Sisay; Mardasa, Kibiru; Wondimneh, Fenta; Teshager, Tilahun; Ketema, Indeshaw (Frontiers in Global Women's Health, 2023)
Background: Malaria is a major public health problem in many developing countries, particularly in sub-Saharan Africa. Malaria during pregnancy endangers the pregnant woman, fetus, and newborn neonate. Hence, insecticide-treated bed net (ITN) use is the most effective and advisable method for preventing malaria during pregnancy. In Ethiopia, studies conducted regarding the prevalence of ITN utilization among pregnant women are inconsistently reported and highly variable. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence of ITN utilization and associated factors among pregnant women in Ethiopia. Methods: A comprehensive search of databases such as PubMed, CINAHL, Web of Science, SCOPUS, Science Direct, and Google Scholar was performed to search for studies conducted in Ethiopia. All original observational studies that reported the prevalence of ITN utilization were identified and screened. The Newcastle-Ottawa scale tool was used to assess the quality of studies. Data were extracted using Microsoft Excel 2010 format and analyzed using STATA Version 14. A random-effect meta-analysis model was utilized to estimate the pooled prevalence of ITN utilization. The statistical heterogeneity was checked using the I2 test and subgroup analysis. The publication bias was assessed using funnel plots and Egger's regression test. The size of the pooled effect of the factors influencing the use of ITNs was estimated using an odds ratio with a 95% confidence interval, and a P-value <0.05 was statistically significant. Results: Twenty-nine cross-sectional studies with 13,957 participants were included. The pooled prevalence of ITN utilization among pregnant women in Ethiopia was 51% (95% CI: 43–60). A statistically significant heterogeneity was observed across studies (I2=99.09%; P<0.001). Being literate [OR=2.93 (95% CI: 2.14–4.01)], rural residence [OR=1.76 (95% CI: 1.37–2.26)], and having knowledge of ITN [OR=4.13 (95% CI: 1.57–10.81)] were factors significantly associated with ITN utilization. Conclusion: The utilization of ITNs among pregnant women was much lower than the national target, alarmingly highlighting the need for urgent interventions. Educational status, place of residence, and knowledge of ITN were predictors of ITN utilization. Health policymakers and programmers should design and implement appropriate strategies to scale up utilization of ITNs by pregnant women and reduce malaria-related morbidity during pregnancy.